The Use of the School Website as a Digital Marketing Strategy in Madrasah - Abid, Saihul; Samsu, Samsu; Jamrizal, Jamrizal (Al-Qalam Institue, 2025)
This study aims to describe and analyze the utilization of the website as a digital marketing strategy at Madrasah Tsanawiyah, focusing on three main aspects: the effectiveness of website utilization, the features and content provided, and the challenges and obstacles encountered during its implementation. The research employs a descriptive qualitative approach with data collected through interviews, observations, and documentation. Informants in this study include the principal, website administrators, social media managers (Instagram and Facebook), teachers, staff, and parents. The data analysis process consists of data collection, data reduction, data presentation, verification, and conclusion drawing. The findings indicate that the school website is quite effective as a promotional tool and information dissemination platform, especially in supporting the student admission process (PPDB). The website includes various features such as registration information, school profile, activity news, and photo galleries. Challenges in its implementation include limited human resources with digital technology expertise, lack of training, infrastructure limitations, and weak integration between work units in managing the school’s digital media. Nevertheless, the website holds significant potential to support the school’s digital marketing strategy, provided it is supported by strengthened human resources, improved infrastructure, and more comprehensive content strategy planning.